2021
DOI: 10.1136/bmjpo-2021-001214
|View full text |Cite
|
Sign up to set email alerts
|

Child alcohol use disorder in Eastern Uganda: screening, diagnostics, risk factors and management of children drinking alcohol in Uganda (TREAT C-AUD): a mixed-methods research protocol

Abstract: BackgroundFollowing a finding of alcohol use among children aged 5–8 years old in Mbale, Uganda, this project investigates the magnitude of alcohol and substance use among children ged 6–13 years old and related household, community, school, health system and clinical factors.MethodsThe project includes four larger work packages (WPs). WP1 comprises management, WP2 and 3 include the scientific components and WP4 includes integration of results, dissemination, policy and implementation advice. This protocol pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Mbale district hosted the TREAT-CAUD project (33), which resulted from an earlier study that found clinically significant alcohol use by children [4]. At the time of data collection Mbale city was within the district and was categorized as urban while the town councils outside Mbale town were categorized as peri-urban.…”
Section: Rationale For Age Range Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mbale district hosted the TREAT-CAUD project (33), which resulted from an earlier study that found clinically significant alcohol use by children [4]. At the time of data collection Mbale city was within the district and was categorized as urban while the town councils outside Mbale town were categorized as peri-urban.…”
Section: Rationale For Age Range Selectionmentioning
confidence: 99%
“…The aim of this study was to translate and adapt the CRAFFT tool into the Lumasaaba language and evaluate its psychometric properties in school-age children aged 6 to 13 years who were at risk for alcohol and other substance use disorders. It was part of the larger Child Alcohol Use Disorder (TREAT C-AUD) project in the Mbale district, Eastern Uganda [ 33 ], that followed the detection of alcohol use by young children [ 4 ]. Specifically, the study aimed to improve the tool’s ability to screen for alcohol and other substances for this vulnerable population in the Ugandan setting.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the use of zero tolerance and danger rhetoric approaches do not re ect the realities the Ugandan children face daily and do not equip them with tools to prevent harm from alcohol consumption (53). The legal drinking age in Uganda is 18, but many children consume earlier (11,13,27,62). The schools could prepare learners with more nuanced and age-appropriate information and contribute to reduced harm.…”
Section: Danger Focused Rhetoricmentioning
confidence: 99%
“…To our knowledge, only few school-based interventions focusing on alcohol have been conducted and assessed in Africa (14,25,26). Previous qualitative studies have described the child and adult perspectives on alcohol use, and some studies have explored the teaching of the standard primary curriculum in Uganda (11,13,(27)(28)(29)(30). The perspectives and experiences with the current standard primary school curriculum on health and alcohol has not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in Mbale district, eastern Uganda, from February to March 2020 just before school closure due to the COVID-19 pandemic. The district hosted the TREAT C-AUD project that investigated the magnitude of alcohol and other drug use among 6-13-year-old children in the health, school and community contexts [31]. At the time of the study Mbale city was a municipal council consisting of three divisions.…”
Section: Design and Settingmentioning
confidence: 99%